The Effect of Special Exercises On The Development Of Launch Angle, Accuracy, Speed of Shooting Free Kick In Advance Beach Soccer - Kazem, Najy; هادي, زيد (Journal of Physical Education, 2017)
The problem of the research lies in the lack of goals from free kick in beach soccer. The researchers designed special exercises for developing the performance, accuracy, speed of scoring as well as launch angle. The aim of the research was designing beach soccer scoring test, designing special exercises for developing the accuracy, speed of launch angle and identifying the effect of these exercises on the accuracy and speed of scoring. The researchers used experimental method. The training program consisted 24 training sessions with three sessions per week for eight weeks. The researchers concluded that the exercises developed the accuracy and speed of scoring as well as launch angle. Finally they recommended training free kicks from all distances and positions.